Beyond Synchronous and Asynchronous Systems towards Blended Learning: Perspective on Medical Education through COVID-19 Pandemic - Aiman Hilmi Asaduddin; Utiya Nabila Maulani (Universitas Indraprasta PGRI, Jakarta, Indonesia, 2021)
Coronavirus Disease 2019 (COVID-19) pandemic affected various aspects, such as the health sector, education, economy, etc., being distracted. This transition requires technology acceleration to maintain the e-learning process across the world, including medical education. E-learning systems, such as synchronous and asynchronous learning, have their own advantages and limitations, especially in medical education that needs theoretical and practical education. In this paper, a new model of mixed synchronous and asynchronous systems towards blended learning was described as an idea for better medical education through the COVID-19 pandemic. Learning systems can be divided into several types prior to previous researches, namely face-to-face learning, blended learning, flipped classroom, Information, and Communication Technology (ICT) supported face-to-face learning, synchronous learning, and asynchronous learning. COVID-19 pandemic forced the education system to full-online system learning, which is synchronous and asynchronous e-learning. In terms of theoretical learning, asynchronous systems may offer flexibility and convenience as well as the system can be used in conditions of time-zone difference, various internet connectivity, and different golden times for each student to learn factual information. However, asynchronous systems also may have a challenge in controlling the students to make sure they follow the class properly. To evaluate students’ progress, educational stakeholders can hold a weekly reflection program asynchronous distance learning. Besides, knowledge practice also can be conducted by focus group discussion (FGD) through synchronous distance learning The synchronous and asynchronous systems provide the students to arrange their schedule more flexible thus can be utilized to learn practical skills in face-to-face education, such as clinical skills and laboratory practices, with strict health protocols. This system will lead to blended learning, which is an online learning and shift-based traditional learning. This approach provides combination systems of asynchronous and synchronous distance learning to support blended learning in terms of lack of practice skills and laboratory competencies.